Flagellar kinesins in protists. (February 2011) - Marande, William; Kohl, Linda
Cilia and flagella are organelles of the cell body present in many eukaryotic cells. Although their basic structure is well conserved from unicellular organisms to mammals, they show amazing diversity in number, structure, molecular composition, disposition and function. These complex organelles are generally assembled by the action of intraflagellar transport, which is powered by kinesin and dynein motor proteins. Several types of kinesins can function in flagella. They all have a well-conserved motor domain with characteristic signatures, but display exhaustive diversification of some domains. This diversity can be explained by the multitude of functions fulfilled by these proteins (transport of cargoes along microtubules, polymerization and depolymerization of microtubules). Functional and phylogenetic analyses reveal that at least seven kinesin families are involved in flagellum assembly and function. In protists, where cilia and flagella fulfill many essential roles, this diversity of function is also observed.